Utopie et langage - Lecercle, Jean-Jacques (Filozofski vestnik, 2018)
The essay seeks to demonstrate that the Utopian impulse has something to do with the structure of human language. It starts by considering the theme of language in three utopias, Bulwer Lytton’s The Coming Race, Hogben’s Interglossa, and Thomas More’s Utopia. From there, it proceeds to analyse the grammar of utopia, with special reference to Paolo Virno’s theory of negation and to the Althusserian concept of interpellation: the utopian impulse corresponds to the moment of counter-interpellation. The operation of utopian counter-interpellation in the visual field is illustrated by an analysis of Annunciation by Previtali.